Application Of Lean Manufacturing Using Value Stream Mapping On Bearing Replacement Process For Electric Motor (Case Study: Pt. Pembangkit Jawa Bali - Pltu Indramayu) - Ikhsan, Abdi Robbi; Haqi, Mitha; Radityo, Muhammad; Primatifar, Daffa; Margana, Riki Ridwan (International Journal of Psychosocial Rehabilitation, 2020)
Electric motor is an equipment that is widely used in industry to support the production process. Inside the electric motor there are components, one of which is bearing. Bearing on an induction electric motor is an important component that functions as a bearing between the shaft surface and the motor housing. Bearing components are not spared from damage so it needs a repair process within a certain period so that the production process is not interrupted for too long. The process of repairing electric motors is one of them is bearing replacement, in the process of bearing replacement can use 2 types of tools, namely heater bearings and bearing fittings. Both of these methods have their own ways at each step of their work and have different durations. Implementation of Lean Manufacturing Using Value Stream Mapping Tools aims to see the whole process of bearing replacement in an electric motor from the beginning to the end of the process and to identify the waste that occurs during the process. The process of replacing the bearings on an electric motor which is currently carried out using a heater bearing tool for the installation process requires a total processing time of 11,445 seconds. And after making improvements to the work process and minimize the waste that occurs then the total time needed for bearing replacement work to be 10.005 seconds.